The IMG/M data management and analysis system v.7: content updates and new features. Issue Volume 51:Issue D1(2023) (16th November 2022) - Chen, I-Min A; Chu, Ken; Palaniappan, Krishnaveni; Ratner, Anna; Huang, Jinghua; Huntemann, Marcel; Hajek, Patrick; Ritter, Stephan J; Webb, Cody; Wu, Dongying; Varghese, Neha J; Reddy, T B K; et al.
Abstract: The Integrated Microbial Genomes & Microbiomes system (IMG/M: https://img.jgi.doe.gov/m/ ) at the Department of Energy (DOE) Joint Genome Institute (JGI) continues to provide support for users to perform comparative analysis of isolate and single cell genomes, metagenomes, and metatranscriptomes. In addition to datasets produced by the JGI, IMG v.7 also includes datasets imported from public sources such as NCBI Genbank, SRA, and the DOE National Microbiome Data Collaborative (NMDC), or submitted by external users. In the past couple years, we have continued our effort to help the user community by improving the annotation pipeline, upgrading the contents with new reference database versions, and adding new analysis functionalities such as advanced scaffold search, Average Nucleotide Identity (ANI) for high-quality metagenome bins, new cassette search, improved gene neighborhood display, and improvements to metatranscriptome data display and analysis. We also extended the collaboration and integration efforts with other DOE-funded projects such as NMDC and DOE Biology Knowledgebase (KBase).